The Effect of ROI and GAF on Regional Expenditures and GRDP (Financial Management Literature Review) - Latif Sholichin (Dinasti International Journal of Management Science, 2023)
Literature article Reviewing the Effect of Regional Original Income (ROI), and General Allocation Funds (GAF) on Regional Expenditures and Gross Regional Domestic Product (GRDP) is a scientific article that aims to build a research hypothesis on the influence between variables that will be used for further research, within the scope of Financial Management Science. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) ROI has an effect on Regional Expenditures; 2) GAF has an effect on Regional Expenditures; 3) ROI has an effect on GRDP; 4) GAF has an effect on GRDP; and 5) Regional Expenditures have an effect on GRDP. Apart from these 2 exogenous variables that affect the endogenous variables of Regional Expenditures and GRDP, there are still many other factors including the variables of Special Allocation Funds, Revenue Sharing Funds, Special Autonomy Funds, and Total Population.